Should I stay or should I go? Romanian migrants during transition and enlargements - Andrén, Daniela; Roman, Monica (Bonn, 2014)
"The change in Romanian political regime in 1989 has lifted the barriers for population circulation and mobility that were further more amplified in 2002 by the liberalization of Romanians' circulation in the Schengen space. In such context, the aim of this paper is to analyze to what extent Romania's accession to the EU in 2007 has added new features to the Romanian migration phenomenon. Therefore, the paper describes characteristics of Romanian labor migration and its labor market outcomes in the context of the EU second enlargement, covering the recent trends and characteristics, as well as the effects on the receiving and origin countries. The restructuring process that accompanied a painful economic transition created severe disequilibria on the labor market, generating a crisis that remains ongoing. From this perspective, migration was and still is the population's response to this crisis and at the same time reduces the unemployment pressure on the Romanian government. Furthermore, in the new context of financial European crisis, the migration outflows didn't reverse and most migrants prefer to develop adjustment strategies in their destination countries. Romania's accession to the EU in 2007 did not generally change the previous characteristics of Romanian migration. However, one of the key features of Romanian migration would be the new wave of the labor mobility of professionals with impacts upon Romanian economy and society."